357PApplication of multi-modal approach to palliation in end of life head and neck cancer pain. (24th November 2019) - Joga, S; Sahi, M S; Koyyala, V P B; Medisetty, P; Jajodia, A; Chaudhari, K; Goyal, S; Bommera, S; Gairola, M
Abstract: Background: Advanced Head and neck cancer despite multimodal treatment is associated with disfigurement, extreme pain, and psychological distress. To study the effects of a multimodal palliative approach involving psychological counselling, psychometric dug therapy and pain-relieving blocks to ameliorate the total pain state of such patient during end of life care. Methods: This is a prospective, single-arm observational study conducted on 20 head and neck cancer patients, from January 2015 to December 2018. Patients who were on palliative treatment were processed for self-report of severe psychological distress and intractable pain by means of innovative distress score and quality of life index and the numeric pain rating scale and given combination therapy with antidepressants, antipsychotics, pain killers and neurolytic blocks along with repeated counselling sessions. Results: 20 patients were included in this study, of which 66.6 % were males and 33.3% were female. Age range was 44-79 years and they had mean pain scores of 7.61 (SD 1.577) before the intervention and mean distress scores of 8.33 (SD 1.237) suffering for a duration of 72.5 days (SD 24.81). A significant reduction in pain was noted by a decrease in mean Numeric rating scale to 2.83 (SD 0.618) and extension of the mean duration of analgesia to 24.33 days (SD 6.84) and reduction in distress score to 3.78 (SD 0.732). Pre- and post-procedure mean morphine requirement was also significantly reduced, at the end of 2 weeks. Significant easing of distress and improvement in performance was observed in all patients. Conclusions: The application of a multimodal palliative approach to progressive head and neck cancer patients is an easy, safe, and cost-effective method to improve quality of life. Medical oncologists must be sensitized to elicit and measure the distress in such patients. Counseling sessions and pharmacotherapy, if indicated, are very effective in the care of such patients. Legal entity responsible for the study: Rajiv Gandhi cancer Institute and Research Centre, New Delhi. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.